Mammalian herbivores in Australia transport nutrients from terrestrial to marine ecosystems via mangroves. (May 2014) - Reef, Ruth; Feller, Ilka C.; Lovelock, Catherine E.
Abstract: Nutrient subsidies from one ecosystem to another serve a critical link among ecosystems. The transfer of materials across the terrestrial-to-marine boundary is considered to be driven by hydrological connectivity, but animal movement can provide another pathway for nutrient transfers. In two separate studies we assessed the role mammals (bats and kangaroos) play in alleviating nutrient limitation in mangrove forests in Australia. At Lizard Island, we measured tree growth and foliar elemental and isotopic composition of trees growing within and outside a large flying fox roost. In Western Australia, we measured foliar elemental and isotopic composition of trees within two forests frequented by kangaroos that feed in spinifex grasslands and shelter in the shade of the mangroves. We compared those with mangroves from adjacent forests that are not frequented by kangaroos. We show that at both locations, the mangrove forest receives terrestrial nutrient subsidies through animal movement. At Lizard Island dominant mangrove species were significantly enriched in nitrogen within the bat roost, as evidenced by higher foliar N concentrations (by up to 150%), N:P and N:C ratios in trees within the roost compared with trees outside the roost. The isotopic signature of foliar N was significantly enriched in 15N by 1–3‰ within the roost, further suggesting that the source of the N enrichment was the bat roost. Growth rates of mangroves within the roost were nearly six times higher than trees outside the roost. In the arid coast of Western Australia, we show elevated foliar 15N abundance of up to 3‰ in mangroves where kangaroos shelter relative to trees where they do not. Thus, this study presents two examples for mammalian herbivore mediated localized transport of nutrients from terrestrial to marine ecosystems, consequently affecting mangrove tree growth, productivity and forest structure.